The period of formation of Independence in Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article covered the modern period of the history of State and Law of the Republic of Kazakhstan. The article highlights the historical and legal developments in recent decades, greatly influenced the formation of the state and law in Kazakhstan. Key words: law, state, civil society, political events.